A 5-Fluorouracil-Induced Hyperammonemic Encephalopathy Challenged with Capecitabine - Michael Chahin; Nithya Krishnan; Hardik Chhatrala; Marwan Shaikh (Case Reports in Oncological Medicine)
Cancer patients presenting with altered mental status demand a broad differential with early recognition of the etiology. Failure to do so is associated with increased morbidity and mortality. Causes that must be considered include organ involvement of the cancer, electrolytes abnormalities, and even chemotherapeutic agents. A 32-year-old female patient had been recently started on FOLFOX for metastatic colon cancer. Her initial treatments were uneventful, but she later developed encephalopathy during day three of cycle five. During her evaluation, she was found to have hyperammonemia (84 mcmol/L), without hepatic failure, that resolved with stopping chemotherapy and supportive care. After a trial of home infusion fluorouracil, she developed hyperammonemic encephalopathy again. During both admissions, her symptoms resolved with IV hydration and cessation of chemotherapy. She was then successfully challenged with capecitabine (1000 mg/m2 daily), and additional hydration, and continued chemotherapy without recurrence of symptoms. Hyperammonemia is associated with fluorouracil though the mechanism is unclear. Suspected etiologies include either elevated levels of the drug due to slower metabolism or accumulation of certain metabolites. Additionally, risk factors such urease-producing bacterial infections, dehydration, and increased catabolism are thought to increase the risk for hyperammonemia. This case demonstrates the need for greater awareness of fluorouracil as a cause of hyperammonemic encephalopathy. Knowledge of this may allow for earlier recognition and reduced unnecessary testing.